Preference Pollution : How Markets Create the Desires We Dislike. (University of Michigan Press, 2009)
Seldom considered is whether markets do an adequate job of shaping our tastes. David George argues that they do not, and that the standard economic definition of efficiency can be used to demonstrate that the market ignores people's desires about their desires. He concludes that markets perform poorly with respect to second-order preferences, thus worsening the problem of undesired desires. The book further investigates changes in perceptions and public policy toward such activities as gambling, credit, entertainment, and sexual behavior. David George is Chair and Professor Economics, LaSalle University.